Physical and Chemical Characteristics of Droppings as Sensitive Markers of Chicken Health Status - Erika Mozuriene; Ernestas Mockus; Dovile Klupsaite; Vytaute Starkute; Ernesta Tolpeznikaite; Valentas Gruzauskas; Romas Gruzauskas; Agne Paulauskaite-Taraseviciene; Vidas Raudonis; Elena Bartkiene (Animals, 2024)
The aim of this study was to analyze the physical and chemical characteristics of chicken droppings (n = 73), which were collected during different age periods and classified by visual inspection into normal (N) and abnormal (A). Significant differences were found in the texture, pH, dry matter (DM), fatty acids (FAs), short-chain fatty acids (SCFAs), and volatile compounds (VCs) between the tested dropping groups (p ≤ 0.05). The age period of the chicken had a significant influence on the color coordinates, texture, pH, DM, and SCFA contents in N and A as well as on all FAs content in N (p ≤ 0.05). Droppings from the N group had a harder texture, lower values of a* and b* color coordinates, higher DM content, higher level of linoleic FA, and lower level of α-linolenic FA than the droppings from the A group in each age period (p ≤ 0.05). The predominant SCFA was acetic acid, the content of which was significantly lower in the N group compared to that of the A group. The alcohol and organic acid contents were the highest in most of the A group at different age periods, while ketones dominated in the N and A groups. In conclusion, the majority of the tested dropping characteristics were influenced by the age period. While certain characteristics demonstrate differences between N and A, a likely broader range of droppings is required to provide more distinct trends regarding the distribution of characteristics across different droppings.